An Investigation Into Factors That Affect Adoption and Diffusion of Innovations in Publishing and Librarianship: A Grounded Theory Approach - Eger, Arthur; Blackey, Haydn (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Getting innovations adopted is often difficult. Not because they lack obvious advantages, but because of the complex nature of the adoption and diffusion process. If everyone included in their strategy, the six elements of the ‘innovation diffusion mix’ identified in this study, adoption and diffusion would be much easier. Parvenir à adopter des changements est souvent difficile. Non pas que ceux-ci sont désavantageux, mais plutôt à cause de la nature complexe des procédures d’adoption et de diffusion. Si chacun pouvait inclure dans sa stratégie, les six éléments de « l’ensemble de diffusion de changements » identifiés dans cette étude, l’adoption et la diffusion seraient beaucoup plus facile à réaliser.